2011
DOI: 10.1111/j.1365-2516.2011.02516.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the management and outcomes of pregnancy in Glanzmann thrombasthenia

Abstract: Glanzmann Thrombasthenia (GT) is a rare autosomal recessive disorder which usually manifests as severe mucocutaneous bleeding and is caused by deficiency of the platelet glycoprotein IIb-IIIa. Pregnancy in women with GT presents particular challenges as there is increased risk of both maternal and foetal bleeding. To improve understanding and clarify the optimum management of pregnancy in this disorder, we performed a systematic review of the world literature of pregnancy and GT. This identified three single-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
105
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(118 citation statements)
references
References 37 publications
(223 reference statements)
2
105
0
11
Order By: Relevance
“…Concerning bleeding in women, we can conclude that menorrhagia has a low frequency (35%), since it occurs only in five women in our cohort, compared to the described frequency in GT [18]. One woman achieved her pregnancy with natural delivery under platelets, while it is rare in a thrombasthenic patient since it often results in important hemorrhage requiring sometimes blood transfusions and threatening the vital prognosis of the mother [19]. For the diagnosis of GT, we use in our laboratory more than one specific test such us LTA which is extremely specific for GT, since platelet fails to aggregate with any agonist [20].…”
Section: Discussionmentioning
confidence: 96%
“…Concerning bleeding in women, we can conclude that menorrhagia has a low frequency (35%), since it occurs only in five women in our cohort, compared to the described frequency in GT [18]. One woman achieved her pregnancy with natural delivery under platelets, while it is rare in a thrombasthenic patient since it often results in important hemorrhage requiring sometimes blood transfusions and threatening the vital prognosis of the mother [19]. For the diagnosis of GT, we use in our laboratory more than one specific test such us LTA which is extremely specific for GT, since platelet fails to aggregate with any agonist [20].…”
Section: Discussionmentioning
confidence: 96%
“…217 Of 40 pregnancies reviewed, three fetuses (7%) died from ICH between 24 and 31 weeks of gestation. 214 The risk is highest in women who have received multiple platelet transfusions, but may also occur in nontransfused women with absent expression of GP IIb/IIIa who develop antibodies when presented with paternally-derived fetal GP IIb/IIIa epitopes.…”
mentioning
confidence: 99%
“…A systematic review 214 showed only partial success with prophylactic platelet transfusion prior to delivery, with PPH in 38% of treated women compared with 63% in women who had not received platelets. Platelets should be HLA-selected, starting with one to two adult doses and further doses depending on observed bleeding.…”
mentioning
confidence: 99%
See 2 more Smart Citations